2006
DOI: 10.1055/s-2006-931574
|View full text |Cite
|
Sign up to set email alerts
|

Conferone from Ferula schtschurowskiana Enhances Vinblastine Cytotoxicity in MDCK-MDR1 Cells by Competitively Inhibiting P-Glycoprotein Transport

Abstract: Overexpression of the protein transporter P-glycoprotein (Pgp, MDR1) at the cell surface is a major cause of multidrug resistance (MDR) and poor response to treatment in cancer chemotherapy and therapy for leishmaniasis. The present study shows that conferone, a sesquiterpene coumarin ether isolated for the first time from Ferula schtschurowskiana, endemic in Uzbekistan, enhances the cell toxicity of vinblastine (VBL) in MDR1-transfected Madin-Darby canine kidney (MDCK-MDR1) cells. Conferone presents the advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…It has been shown that conferone, isolated from Ferula schtschurowskiana, enhances the cytotoxicity of vinblastine by competitively blocking the P-gp transport, which was shown by decreasing the P-gp photolabeling effi ciently. Conferone, the fi rst identifi ed natural sesquiterpene coumarin from Ferula, is a promising drug candidate for reversion of MDR encoded by the MDR1 gene (Barthomeuf et al, 2006). The capacity of conferone to bind P-gp with high affi nity is in agreement with the observation that a binding site for sesquiterpenes exists within the transmembrane domain of P-gp (Munoz-Martinez et al, 2004).…”
Section: Morphological Alterationsmentioning
confidence: 53%
See 1 more Smart Citation
“…It has been shown that conferone, isolated from Ferula schtschurowskiana, enhances the cytotoxicity of vinblastine by competitively blocking the P-gp transport, which was shown by decreasing the P-gp photolabeling effi ciently. Conferone, the fi rst identifi ed natural sesquiterpene coumarin from Ferula, is a promising drug candidate for reversion of MDR encoded by the MDR1 gene (Barthomeuf et al, 2006). The capacity of conferone to bind P-gp with high affi nity is in agreement with the observation that a binding site for sesquiterpenes exists within the transmembrane domain of P-gp (Munoz-Martinez et al, 2004).…”
Section: Morphological Alterationsmentioning
confidence: 53%
“…Several studies have shown that some drimane-type sesquiterpene coumarins such as conferone, mogoltacin and diportlandian ( Fig. 1) can increase the drug accumulation and effectiveness by P-glycoprotein inhibition (Barthomeuf et al, 2006;Behnam Rassouli et al, 2009;Munoz-Martinez et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that this compound significantly inhibited the extrusion of the rhodamine123 and the radiolabeled anti-cancer agent [ 3 H]-vinblastine out of MDR1-transfected Madin-Darby canine kidney (MDCK-MDR1) cells, via competitive inhibition of P-gp transport activity 102 . It is notable that the proportion of killed MDCK-MDR1 cells (normal cell line), reached 93%, when vinblastine was used in combination with cnidiadin at 10 mM.…”
Section: Coumarinsmentioning
confidence: 99%
“…They isolated 11 sesquiterpene derivatives and among them were two sesquiterpene coumarins: farnesiferol A (18) and feselol (22). Based on previous reports on the potential role of sesquiterpene coumarins as reversal agents of multidrug resistance (MDR) in cancer cells (Barthomeuf et al 2006), the authors studied the interactions of the isolated compounds with efflux pumps. Using the parasitic model of the P-glycoprotein nucleotide-binding domain of MDR-like efflux pump in Cryptosporidium parvum, they confirmed the chemotherapeutic potential role of farnesiferol A (18) (IC 50 = 24.9 lM) and feselol (22) Farnesiferol B (19), farnesiferol C (20) and two other sesquiterpene coumarins, microlobidene (23) and kellerin (24), were isolated from the F. assafoetida gum resin and tested as antiviral agents (Rollinger et al 2008).…”
Section: Sesquiterpene Umbelliferyl (7-hydroxycoumarin) Ethersmentioning
confidence: 99%